De l'inefficacité du réseau social – Des liens sociaux non mobilisés chez les patients atteints de cancer. Issue 121 (January 2014) - Defossez, Adrien
The Ineffectiveness of a Social Network – Non-mobilized Social Ties among Cancer Patients : Many social network studies concern resources that an individual may have access to through social relationships. By focusing on networks that have "worked", these studies try to specify the factors that enabled access. But few studies have examined the networks that failed to provide the goods or the service desired. This article discusses these "ineffective" networks through the case of cancer patients seeking information about their pathology. The results indicate that the causes of the inefficiency of the network are to be found in non-mobilization of links by the patients of the study. A certain number of constraints on these links prevent their mobilization.